ESMO–ESGO–ESTRO consensus conference on endometrial cancer: Diagnosis, treatment and follow-up. Issue 3 (December 2015) - Colombo, Nicoletta; Creutzberg, Carien; Amant, Frederic; Bosse, Tjalling; González-Martín, Antonio; Ledermann, Jonathan; Marth, Christian; Nout, Remi; Querleu, Denis; Mirza, Mansoor Raza; Sessa, Cristiana; ,
Abstract: The first joint European Society for Medical Oncology (ESMO), European SocieTy for Radiotherapy & Oncology (ESTRO) and European Society of Gynaecological Oncology (ESGO) consensus conference on endometrial cancer was held on 11–13 December 2014 in Milan, Italy, and comprised a multidisciplinary panel of 40 leading experts in the management of endometrial cancer. Before the conference, the expert panel prepared three clinically-relevant questions about endometrial cancer relating to the following four areas: Prevention and screening, surgery, adjuvant treatment and advanced and recurrent disease. All relevant scientific literature, as identified by the experts, was reviewed in advance. During the consensus conference, the panel developed recommendations for each specific question and a consensus was reached. Results of this consensus conference, together with a summary of evidence supporting each recommendation, are detailed in this article. All participants have approved this final article.